MODELING OF STONE PHYSICS FOR THE CHARACTERIZATION OF ORGANIC BATHERS IN THE SOUTH SUMATERA - LUTFI RAMADHAN (NIM: 22317017), MUHAMAD
Oil and gas production in Indonesia has declined in last few years due to the decrease of conventional reserves. Therefore oil and gas industry needs to start exploring and developing unconventional reservoir, such as shale oil and shale gas. Shale oil or gas can be originally found within the source rock, organic-rich shale. This reservoir is intrinsically complex as it may contain kerogen that can significanly affect rock elastic properties. Study on rock physics modeling can help improving our understanding in order to characterize the organic-rich shale. The objective of this research is to build a modified rock physics model for organic-rich shale based on previous studies to quantify the effect of kerogen and kerogen porosity on elastic properties. The model uses Voigt-Reuss-Hill bounding method, Kuster-Toksoz and Self-Consistent Approximation inclusion theories, and Gassmann fluid replacement in calculating rock properties. The model has been initially tested on a synthetic data, then it is applied further to a log data from well RMDN in South Sumatera Basin, where the organic shale of Gumai Formation consists at 4800-6000 feet as a potential source rock. Because of the limited log information, estimation of mineral fraction and properties, porosity, and total organic carbon (TOC) had to be made first using petrophysical calculation. Rock physics modeling shows a good correlation between observed and calculated data at around 0.6 for Vp, 0.72 for Vs, and 0.99 for density. The result also indicates that the model and workflow used in this research can be used to describe the behavior of organic-rich shale quiet well.